A polymorphism in a major antioxidant gene (Kelch-like ECH-associated protein 1) predicts incident cardiovascular events in chronic kidney disease patients: an exploratory study. Issue 5 (May 2016) - Testa, Alessandra; Leonardis, Daniela; Spoto, Belinda; Sanguedolce, Maria Cristina; Parlongo, Rosa M.; Pisano, Anna; Tripepi, Giovanni; Mallamaci, Francesca; Zoccali, Carmine
Abstract : Supplemental Digital Content is available in the text Abstract : Objective: Oxidative stress is considered a major pathway conducive to cardiovascular disease in chronic kidney disease (CKD) patients. However, observational studies and clinical trials testing this relationship are controversial. The Nuclear factor-erythroid-2-related factor 2 (Nrf2)-Kelch-like ECH-associated protein 1 (Keap1) system is a major system regulating antioxidant mechanisms in living organisms. Owing to the fact that genes are transmitted randomly (Mendelian randomization), genetic variants may provide unconfounded assessment of putative causal risk factors. Methods: We have therefore explored the association of eight polymorphisms in the Nrf2 gene and three polymorphisms in the Keap1 gene (capturing over 80% of the genetic variance in the same genes) with cardiovascular events in a multicenter cohort study of 758 CKD patients. Results: During the follow-up period, 117 patients had fatal and nonfatal cardiovascular events and 42 died. The hazard rate of fatal and nonfatal cardiovascular outcomes was about twice higher in patients with the AA or the CA genotype (dominant model) in the rs110857735 polymorphism of the Keap1 gene (hazard rate: 1.85, 95% CI: 1.20–2.84, P  = 0.005) than in those with the CC genotype. Further analyses adjusting for Framingham risk factors and CKD-specific risk factors and a bootstrapping validation analysis did not modify the strength of this association. No association was registered between other Keap1 and Nrf2 polymorphisms and cardiovascular disease in the same cohort. Conclusion: In this exploratory study a gene-variant in Keap1, a major gene regulating the antioxidant response, predicts incident cardiovascular events in CKD patients. This finding is in keeping with the hypothesis implicating oxidative stress in cardiovascular disease in this population.